Experimental research of extended polarization coherence theorem for nonclassical light - Jara Ortiz, Max (Pontificia Universidad Católica del Perú, 2023)
This thesis reports the experimental display of an extension of the polarization coherence theorem (PCT), a theorem that established a constraint between distinguishability and visibility, two quantities that serve, respectively, as a measure of particle-like and wave-like behavior that may simultaneously appear in interferometric arrangements. While the PCT applies in both quantum and classical regimes, this thesis focuses on the quantum case. The experiments were conducted using single photons. The theoretical extension of the PCT that was submitted to experimental test is much more involved than the original PCT and put several technical challenges. This thesis reports the successful implementation of the experiments. The techniques used could also be employed, with slight modifications, when working with classical light. The general framework, in which our results make a contribution, refers to so-called wave-particle duality and Bohr’s complementarity principle. This is a topic of intensive research that addresses not only foundational issues in quantum mechanics but also practical applications in quantum information science.

Esta tesis reporta la demostración experimental de una extensión del teorema de la coherencia de polarización (PCT), un teorema que estableció una restricción entre la distinguibilidad y la visibilidad, dos cantidades que sirven, respectivamente, como medida de el comportamiento de el tipo partícula y de el tipo onda los cuales pueden aparecer simultáneamente en los arreglos interferométricos. Si bien el PCT se aplica tanto en el régimen cuántico como en el clásico, esta tesis se centra en el caso cuántico. Los experimentos se llevaron a cabo con fotones individuales. La extensión teórica de la PCT que se sometió a prueba experimental es mucho mas complicada que la PCT original y planteó varios retos técnicos. Esta tesis informa de la exitosa realización de los experimentos. Las técnicas utilizadas también podrían emplearse, con ligeras modificaciones, al trabajar con luz clásica. El marco general, al que contribuyen nuestros resultados, se refiere a la llamada dualidad onda-partícula y al principio de complementariedad de Bohr. Este es un tema de intensa investigación que aborda no solo cuestiones fundamentales de la mecánica cuántica, sino también aplicaciones prácticas en la ciencia de la información cuántica.
Keywords: Coherencia (Física); Polarización (Física nuclear); https://purl.org/pe-repo/ocde/ford#1.03.00